PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUIPENDEKATAN MATEMATIKA REALISTIK - Risna Mira Bella Saragih (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
The problem in this research is low student problem solving skills and students are not accustomed to solving problems with various procedures. This study aimed to determine (1) the differences increase students' problem-solving. (2) Determine the pattern of answers that the students in solving problems in each lesson. This study is a quasi-experimental, with research samples of class VII Budi Satrya SMP and SMP Al-Azhar Medan. Instruments used in math problem solving tests. Those instruments have been declared eligible content validity, and reliability coefficient of 0.95. Data analysis was performed with t test and Mann Withney. The main result of this study was (1) there is a difference improving problem-solving abilities of students who obtain realistic mathematics learning approach with students who get regular learning approach. Increased ability to understand the experimental class problem with categories is 0.51, while the control class at 0.28 with a low category. Improved ability to plan completion of the experiment class was 0.54 with a category of approximately 0.33 while the control class with the medium category. Increased ability to perform calculations experimental class at 0.47 with medium category, while the control class at 0.28 with a low category. Increased ability to re-examine experimental class 0.44 medium category, while the control class 0.22 with a lower category. (2) The pattern of responses of the students in learning mathematics with a realistic approach to obtain better results compared to the pattern of responses of the students in learning with the usual approach. Suggestions for teachers are (1) Learning with a realistic mathematical approach can be used as an alternative for teachers of mathematics in presenting the subject matter of mathematics. (2) Learning with a realistic mathematical approach should be applied to the essential material regarding the real objects around the place to learn, to make students more quickly understand the lessons being learned. (3) In every lesson the teacher should create a learning atmosphere that gives the opportunity for students to express mathematical ideas in their own language and ways, so in mathematics learning to be brave argued, more confident and creative. While the advice to the researchers continued, should this research can be equipped with a detailed study of other aspects that have not been reached in this study.